2023
DOI: 10.1038/s41377-023-01234-y
|View full text |Cite
|
Sign up to set email alerts
|

Universal linear intensity transformations using spatially incoherent diffractive processors

Abstract: Under spatially coherent light, a diffractive optical network composed of structured surfaces can be designed to perform any arbitrary complex-valued linear transformation between its input and output fields-of-view (FOVs) if the total number (N) of optimizable phase-only diffractive features is ≥~2NiNo, where Ni and No refer to the number of useful pixels at the input and the output FOVs, respectively. Here we report the design of a spatially incoherent diffractive optical processor that can approximate any a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…For a phase-only diffractive network, i.e., only the phase profile of each diffractive layer is trainable, the sufficient condition becomes N2NiNo due to the reduced degrees of freedom within the diffractive volume. Similar conclusions can be reached for a diffractive network that operates under spatially incoherent illumination: Rahman et al 26 . demonstrated that a diffractive network can be optimized to perform an arbitrary nonnegative linear transformation of optical intensity through phase-only diffractive processors with N2NiNo.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…For a phase-only diffractive network, i.e., only the phase profile of each diffractive layer is trainable, the sufficient condition becomes N2NiNo due to the reduced degrees of freedom within the diffractive volume. Similar conclusions can be reached for a diffractive network that operates under spatially incoherent illumination: Rahman et al 26 . demonstrated that a diffractive network can be optimized to perform an arbitrary nonnegative linear transformation of optical intensity through phase-only diffractive processors with N2NiNo.…”
Section: Introductionsupporting
confidence: 58%
“…S1 in the Supplementary Material), forming complex-number-based images. To accurately model the spatially incoherent propagation 26 of light through the D2NN, we averaged the output intensities over a large number of Nφ=20,000 of randomly generated 2D phase profiles at the input (see Sec. 4 for details).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations